THE EFFECT OF LEVERAGE, PROFITABILITY, AND ECONOMIC CONDITIONS ON THE RETURNS OF CORPORATE IJARAH SUKUK DURING THE 2015-2018 PERIOD - Meidina Ana Ogie; Nisful Laila (Universitas Airlangga, 2020)
This research intends to analyze the impact of the variables of Debt to Equity Ratio (DER), Return on Asset (ROA), inflation and interest rates on returns of corporate ijarah Sukuk during the period of 2015-2018. The data gathered for this research is from the Financial Statements derived from the official website of each Company, Statistical Bureau Agency (BPS), Indonesia Price Bond Agency (IPBA) and Bond Book published by Financial Services Authority (OJK). The method of analysis used is the panel data regression analysis. The sample collected purposive sampling method is 18 Sukuk which are from 4 Sukuk publishing companies. The best model to process the data is the Random Effect Model. The result of the study shows that all variables affect the Sukuk yields simultaneously; however, the DER variable has a significant positive effect on Sukuk yields partially. Meanwhile, the ROA variable and inflation are not significant negative and interest rates have a negative effect significant to Sukuk yields. Keywords: Debt to Equity Ratio (DER), Return on Assets (ROA), Inflation, Interest Rates, Sukuk ReturnsREFFERENCE Alfiani, Damalia. (2013). Pengaruh likuiditas, produktivitas, provitabilitas, dan leverage terhadap peringkat sukuk (studi empiris pada bank umum syariah dan usaha unit syariah periode 2008-2010. Accounting Analysis Journal, 2(1), 110-115.Boediono. (1995). Seri sinopsis pengantar ilmu ekonomi no. 2: Ekonomi makro. Edisi Keempat. Yogyakarta: BPFE.Fahmi, Irham. (2012). Analisis laporan keuangan. Cetakan kedua. Bandung: Alfabeta.Housten, Brigham. (2010). Dasar-dasar manajemen keuangan edisi 1 buku 1. Jakarta: Salemba Empat.Kasmir. (2008). Analisis laporan keuangan. Jakarta: Rajawali Pers.Kadir, Syamsir. (2007). Pengaruh faktor struktural dan fundamental ekonomi terhadap tingkat imbal hasil obligasi korporasi di pasar modal Indonesia. Disertasi tidak diterbitkan. Bandung: Program Doktor Ilmu Ekonomi Universitas Padjajaran.Kuncoro, Mudrajat. (2004). Metode kuantitatif: teori dan aplikasi untuk bisnis dan ekonomi. Yogyakarta: UPP AMP YKPN.Mansur, M. (2009). Pengaruh tingkat suku bunga SBI dan kurs dolar AS terhadap indeks harga saham gabungan bursa efek Jakarta periode tahun 2000-2002. Working Paper in Accounting and Finance.Muhammad. (2014). Manajemen keuangan syariah. Yogyajkarta: UPP STIM YKPN.Rahardjo, Budi. (2009). Dasar-dasar analisis fundamental saham laporan keuangan perusahaan. Yogjakarta: Gajah Mada University Press.Ratih dan Nur Cahyono. (2014). Analisis faktor-faktor yang mempengaruhi peringkat obligasi. Diponegoro Journal of Accounting, 1(1), 1-13.Rosadi, Dedi. (2011). Analisis ekonometrika dan runtut waktu terapan dengan R. Yogyakarta: Andi Offset.Rendragraha, Bhirawa. (2012). Pengaruh faktor fundamental terhadap return saham pada emiten Jakarta Islamic Index tahun 2005-2011. Skripsi tidak diterbitkan. Surabaya: Fakultas Ekonomi dan Bisnis Universitas Airlangga.Sari, Naluritha, Ni Wayan Linda, dkk. (2015). Variabel-variabel yang mempengaruhi yield obligasi pada perusahaan yang terdaftar di Bursa Efek Indonesia. E-Jurnal Manajemen Unud, 4(11), 3796-3824.Sudana, I Made. (2009). Manajemen keuangan teori dan praktik. Surabaya: Airlangga University Press.Sugiyono. (2014). Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung: Alfabeta.Tandelilin, E. (2010). Portofolio dan investasi teori dan aplikasi. Edisi Pertama. Yogyakarta: KanisiusZiebart, David A dan Reiter, Sara A. (1992). Bond Ratings, Bond Yields and Financial Information, Contemporary Accounting Research, 9(1), 252-282.